Research of neuroprotective properties of TrkA-receptor agonist GK-2 on model of oxidative stress in human vascular endothelial cells (HUVEC) - T. A. Antipova; S. V. Nikolaev; S. A. Kryzhanovsky; E. S. Pekeldina (LLC "Publisher OKI", 2019)
Oxidative stress resulted to decrease in cells viability compared to the control (78 ± 5 % and 100 ± 6 %, respectively, р < 0,05). GK-2 and NGF prevented H2O2-induced HUVEC cells damages (95 ± 3 % for HA-2 and 97 ± 4 % for NGF vs. 78 ± 5 % for H2O2, p < 0.05). In control the number of cells with condensed chromatin was 9 ± 2, after the addition of H2O2 78 ± 9 (p < 0.05 compared with the control). The addition of NGF or GK-2 after H2O2 significantly reduced the number of such cells (44 ± 9 and 41 ± 8, respectively) (p < 0.05 compared to hydrogen peroxide) and prevented the development of morphological changes in nuclear chromatin. Thus GK-2, like NGF, in human endothelial cell culture HUVEC prevented the apoptosis development caused by hydrogen peroxide.